Istikhdam Namudzaj al-Ta’allum al-Ta’awuniy bi Uslub Dakhil Dairah wa Kharijiha fi Ta’lim al-Mufradaat li Tarqiyah Istiy’ab Mufradaat al-Talamidz fiha / Using the Cooperative Learning Model with Inside and Outside the Circle Method in Vocabulary Teaching to Improve Students' Vocabulary Comprehension - Siti Sanah; Agus Karim; Rayhan Muhamad Ridwan (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2024)
The inside outside circle cooperative learning model is a model that assumes that students are able to interact with each other and actively participate in the thinking process and teaches students to respect each other in learning activities so that the material can be well understood by the students equally. Use this model also in all subjects including learning Arabic. The purposes of this research are to know the improvement of students' ability to mastery Arabic vocabulary before and after using the cooperative learning model by inside outside circle in teaching vocabularies, and to know the improvement of their ability by using the cooperative learning model by inside outside circle in teaching vocabularies. The method used is a pra-experimental method with one group design, pre-test and post-test. Among the results obtained is the ability of students to mastery Arabic vocabularies before using the cooperative learning model by inside outside circle at 9th grade B Al-jawami Islamic Junior High School Cileunyi Bandung indicates a low score, as indicated by the average value of 47,6 and this result is in a low degree because the score is between 0-59 in the standard of interpretation. And after using the cooperative learning model by inside outsdie circle at 9th grade B Al-Jawami Islamic Junior High School, it indicates a high degree, as indicated by the average value of 90,6, and this result is in a high degree because the score is between 80-100 in the interpretation criterion. And the use of the cooperative learning model by inside outside circle in teaching vocabularies affects students' ability to mastery Arabic vocabularies.المستخلص: نموذج التعلم التعاوني بأسلوب داخل الدائرة و خارجها هو نموذج يفترض أن التلاميذ قادرون على التفاعل مع بعضهم البعض ويشاركون بنشاط في عملية التفكير ويعلم التلاميذ احترام بعضهم البعض في أنشطة التعلم بحيث يمكن فهم المواد جيدًا من قبل التلاميذ بالتساوي. و أغراض هذا البحث هي لمعرفة ارتقاء قدرة التلاميذ على استيعاب مفردات قبل استخدام نموذج التعلم التعاوني بأسلوب داخل الدائرة و خارجها في تعليم المفردات و بعد استخدامه و لمعرفة ارتقاء قدرتهم باستخدام نموذج التعلم التعاوني بأسلوب داخل الدائرة و خارجها في تعليم المفردات. و الطريقة المستخدمة هي طريقة ما قبل تجربة بتصميم مجموعة واحدة الاختبار القبلي والاختبار البعدي. ومن النتائج المحصولة هي قدرة التلاميذ على استيعاب مفرادات قبل استخدام نموذج التعلم التعاوني بأسلوب داخل الدائرة و خارجها لتلاميذ الصف التاسع الباء بمدرسة الجوامع المتوسطة الإسلامية شيلنجي باندونج تدل على درجة منخفضة، كما دلت على قيمة المتوسط 47,6 في درجة منخفضة لأنها تقع بين 0-5,9 في معيار التفسير. و بعده تدل على درجة مرتفعة، كما دلت على قيمة المتوسط 90,6 و هذه النتيجة في درجة مرتفعة لأنها تقع بين 80-100 في معيار التفسير. و استخدام نموذج التعلم التعاوني بأسلوب داخل الدائرة و خارجها في تعليم المفردات يؤثر في قدرة التلاميذ على استيعاب المفردات.